AI-powered Somatic Cancer Cell Analysis for Early Detection of Metastasis: The 62 principal Cancer Types - Sandile Buthelezi; Solly Matshonisa Seeletse; Taurai Hungwe; Vimbai Mbirimi-Hungwe (International Journal of Integrated Health Sciences)
Background: Early detection of metastasis is critical in improving survival outcomes in cancer patients, with artificial intelligence offering advanced tools for predictive analytics.